Edukasi Standarisasi Mutu melalui Penyuluhan CPPOB dan SOP di Mitra Paguyuban Dawet Ayu Banjarnegara - Nurul Latifasari; Ratih Windu Arini; Yulian Zetta Maulana; Salimatul Qolbiyah; Hanun Khoirunisa (Politeknik Piksi Ganesha Indonesia, 2026)
The Banjarnegara Dawet Ayu Association, an icon of traditional regional beverages, still faces various obstacles in business development, such as limited knowledge regarding the implementation of food safety through Good Manufacturing Practices (GMP) and Standard Operating Procedures (SOPs). This community service activity aims to improve product quality and competitiveness through outreach on the implementation of Good Manufacturing Practices (GMP) and Standard Operating Procedures (SOPs). The methods used include delivering material on food safety, GMP, and SOPs, followed by assistance in preparing SOP documents, and evaluation through pre-tests and post-tests. The results of the activity showed a 27.9% increase in participant knowledge, from 57.3% to 85.2%, indicating that participants were able to absorb the information well. Significant improvements were seen in understanding aspects of food safety and the purpose of implementing SOPs, as well as the importance of GMP in maintaining product quality and safety. This success proves that strengthening partner capacity through education and direct practice can improve understanding and skills in production and business strategy. Thus, this dedication is expected to encourage the Banjarnegara Dawet Ayu Association to produce higher quality, safer, and more competitive products, as well as being able to develop marketing strategies systematically and sustainably.